Novel use of hysteroscopy in the assessment of tubal patency in difficult cannulation - Kaberi Banerjee; Bhavana Singla (Wolters Kluwer Medknow Publications, 2021)
The objective was to assess the method of chromopertubation (CPT) in cases of difficult cannulation to minimize the false-negative cases of tubal block. We had performed laparoscopy and hysteroscopy in 66 females as infertility workup. In all these females, cannulation through the cervical canal was difficult and tubal patency test showed tubal block with Leech-Wilkinson cannula. Then, through the inlet of hysteroscope, methylene blue dye was injected and the patency of tubes was assessed again. In 59 out of the 66 females, we observed that when cannulation and dilation of cervix was difficult, then CPT with hysteroscope showed positive tubal patency test. Introduction of hysteroscope with visualization bypasses cervical factor and reduces false-negative results of tubal patency that is an added advantage of hysteroscope that has not been reported earlier.